The Impacts of Bali cultural Tourism to the Local Balinese Community - Widhiastuty, Ni Luh Putu Sri; Murdana, I Ketut (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
The purpose of this article is to analyze the impact of Bali's cultural tourism on the local Balinese community. This research employs a qualitative approach through a literature study, where the data sources used are secondary data. The main data sources are various types of literature such as books, scientific journals, articles, and reports. Data collection is carried out by reading, taking notes, quoting, and analyzing the content of these sources. Data analysis is performed through content analysis and synthesis or consolidation of findings from various sources. The results of the discussion in the article indicate that there are two major impacts of the existence of Bali's cultural tourism on the local Balinese community. These impacts are positive and negative impacts.